1990
DOI: 10.1111/j.1439-0450.1990.tb01040.x
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Diarrhea Associated with Campylobacter hyointestinalis

Abstract: Summary An enteric disease affected 16 ruminating calves. The disease was characterized by a nonspecific, mild to severe diarrhea and wasting. Two calves died during the course of disease. C. hyointestinalis was isolated from 12 to 14 calves. The antibody titers of affected calves to C. hyointestinalis varied from 1 : 20 to 1 : 160. The disease was successfully treated with chloramphenicol. Zusammenfassung Bovine Diarrhoe im Zusammenhang mit Campylobacter hyointestinalis 16 wiederkäuende Kälber erkrankten an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…The presence of ST50 was associated with diarrhea at the time of sampling in calves. Although some authors ( Al-Mashat and Taylor, 1983 ; Diker et al, 1990 ; Schulze, 1992 ) suggested a possible role of Campylobacter in calf diarrhea, in other studies no association between C jejuni and disease was given ( De Rycke et al, 1986 ; Acha et al, 2004 ), as was also true for the calves of the present study ( Klein et al, 2013 ) and more likely other pathogens generally associated with calf diarrhea may be the cause of disease.…”
Section: Discussionmentioning
confidence: 43%
“…The presence of ST50 was associated with diarrhea at the time of sampling in calves. Although some authors ( Al-Mashat and Taylor, 1983 ; Diker et al, 1990 ; Schulze, 1992 ) suggested a possible role of Campylobacter in calf diarrhea, in other studies no association between C jejuni and disease was given ( De Rycke et al, 1986 ; Acha et al, 2004 ), as was also true for the calves of the present study ( Klein et al, 2013 ) and more likely other pathogens generally associated with calf diarrhea may be the cause of disease.…”
Section: Discussionmentioning
confidence: 43%
“…The distinction and definition at the genetic and phenotypic level is not trivial (Moolhuijzen et al 2009), but some useful approaches have been described (On and Harrington 2001). C. hyointestinalis has been associated with bovine diarrhea (Diker et al 1990) and digestive tract infection in cattle (Bryner et al 1964;Hum 1996).…”
Section: Significance Of Campylobacters In Animal Diseasementioning
confidence: 98%
“…Campylobacter jejuni is the most common cause of bacterial gastrointestinal disease in many western industrialized countries (Tauxe, 1992). In contrast to most other animals, in which Campylobacter does not cause any symptoms, Campylobacter species, especially C. jejuni, may cause diarrhea in calves (Diker et al, 1990;Schulze, 1992). In addition to the potential risk of Campylobacter in contributing to enteritis in calves, calves might act as a reservoir for Campylobacter spp.…”
Section: The Genus Campylobactermentioning
confidence: 99%